PERBEDAAN STRATEGI READING ALOUD DENGAN TWO STAY TWO STRAY TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS EKONOMI KELAS 8 SMP NEGERI 12 PAREPARE - ., Subhan (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2019)
Research Objectives is the purpose to find out 1) Students' learning outcomes on subjects IPS Economics with the application of Reading Alound Strategy on 8th grade students of SMP Negeri 12 Parepare; 2) Student learning outcomes in Economic IPS subjects with the application of Two Stay Two Stray Strategy on 8th grade students of SMP Negeri 12 Parepare and 3) Differences in students' IPS learning outcomes between the application of Reading Alound Strategy and Two Stay Two Stray in Grade 8 students of SMP Negeri 12 Parepare. This research is a quasi experimental research (quasi experiment) with pretest posttest equivalent group design (pretest post group design). The subjects of this study were the eighth grade students of the even semester of the 2017/2018 lesson year that the division; class 8.1 amounted to 22 people and class 8.2 amounted to 23. This study was conducted in 3 meetings. Data collection techniques in this study using observation sheets, tests and documentation. Instrument validity test is performed by expert judgment and for test questions using item analysis by calculating the level of difficulty and different power. Furthermore, the reliability test is calculated using the formula KR-21. For prerequisite analysis test, normality test using Kolmogorov-Smirnov test and for homogeneity test using Levene test. Data analysis techniques for hypothesis testing using the formula-t test polled variance two independent samples. The results showed that: 1) Learning outcomes with Reading Alound Strategy at the time of pretest known the average value of the result is still that is 66.74 while at the posttest of 70.65. 2) Learning outcomes with Two Stay Two Stray Strategy at the time of pretest is 72,39. At postest it is known that the average yield value is 82.83. 3) There is difference of learning result value with Reading Alound Strategy with Two Stay Two Stray Strategy at Grade 8 students of SMP Negeri 12 Parepare. This can be seen from the results of hypothesis testing using the test-t polled variance at the student's posttest value menunjuukan that thitung is equal to 2.097 larger than the ttabel whose magnitude is 1.994.